Acquired Brown Syndrome in Head Trauma: Does Fixation of Associated Nasal and Frontal Bone Fractures Provide a Cure?. Issue 1 (30th January 2020) - Watts, Mark; McQuillan, Joe; Holmes, Simon
A 43-year-old gentleman presented with vertical double vision following nasal and frontal bone fractures resulting from blunt trauma to the glabella. Orthoptic assessment revealed a diagnosis of traumatic Brown syndrome affecting the right eye. The fractures were fixed with open reduction internal fixation via a coronal flap nine days after the injury was sustained. Evidence of resolution of the syndrome became apparent clinically within 15 days following surgery, which was confirmed with a later orthoptic evaluation. This case demonstrates that prompt surgical intervention of fractures associated with traumatic Brown syndrome may lead to resolution without the need to resort to extraocular muscle surgery.